The Role of Medical Records in the Implementation of the EFQM Model in Hospital - Nilufar Masouri; Fateme Sadeghi; Elham Khayyamdar (Tehran University of Medical Sciences, 2011)
Background and Aim: Information is a factor for organizations success and organizations try to stay in this competitive world. In each organization, there are sections that have special role in information aspect in hospitals and healthcare centers, this role is for medical record section which organizes all of the patients' health care information. Paying attention to function quality in this section(medical record) is very important. Since health ministry introduce(EFQM) as an Excellence Model for hospitals, there fore, the role and importance of medical record section in implementation of this model and its criteria is determined. Materials and Methods: All of the information databases was collected and those which were appropriate were selected. Then according to the article's goal, proper keywords were selected and documented through comparing with MESH. Finally related articles in credible journals were used in two Persian and English languages. Results: After determining all the concepts and criteria of EFQM and matching them to the medical record section's goals, task's and functions, feasibility study of EFQM implementation in medical record section, is approved. With this comparism, importance of this section's role in signification model scores hospitals quality of performance is determined.